Consumer response to hemp: A case study of Vermont residents from 2019 to 2020. Issue 4 (26th December 2020) - Kolodinsky, Jane; Lacasse, Hannah
Abstract: Hemp has emerged as a novel crop and ingredient for sustainable products. If innovative hemp‐based products are to succeed in the market, the surge of interest in production must be accompanied by information generation across the supply chain. At present, there is little knowledge on consumer behavior toward hemp and hemp‐based products, and even less on how this behavior has changed since hemp's reintroduction to the production landscape of the United States in 2014. This study compares representative survey data of Vermont residents in 2019 and 2020 on their support for hemp production, and awareness and use of hemp‐based products. Although the influence of demographic variables did not significantly change over time, our findings reveal structural change, with more respondents aware of and using hemp‐based products in 2020 compared to 2019. These findings point to hemp's growing presence and acceptance in the marketplace, where consumers are more informed about or have greater access to hemp products. Despite the state's focus on cannabidiol production, Vermonters appear to be aware of and are purchasing a variety of hemp goods, such as clothing and paper. Abstract : This study compares representative survey data of Vermont residents in 2019 and 2020 on their support for hemp production, and awareness and use of hemp‐based products. Although the influence of demographic variables did not significantly change over time, our findings reveal structural change, with more respondents aware of and using hemp‐based products in 2020 compared to 2019. These findings point to hemp's growing presence and acceptance in the marketplace, where consumers are more informed about or have greater access to hemp products.